MAKNA PANGGILAN DAN PILIHAN DALAM SURAT 2 PETRUS 1:10-11 - David Susilo Pranoto (Manna Rafflesia, 2015)
2 Peter 1: 10-11 gives an explanation to Christians in Asia to try to be even more determined about their vocation and choices. Because when they do it, it will never fall or stumble. Seriousness becomes the most important thing to fulfill the call. A call is not an invitation whose source is from one's own person, but God calls him so that no one can reject a call coming from God. The choice that God has set for someone is the most beautiful gift. Therefore, by learning the meaning of vocations and choices will be able to foster God's deep gratitude and love in believers.